Provincial economic governance in Vietnam : (The Asia Foundation, 2005)
This research report suggests that the decentralisation of certain economic powers from central to provincial government has contributed to this success. Allowing provinces to find their own way forward was central to Vietnam’s progress in institutional and economic development. Decentralisation brought about a number of inefficiencies, but these are outweighed by the gains resulting from policy experimentation at the provincial level.